EFFECTIVENESS OF BETA BLOCKERS ON PATIENTS WITH CIRRHOSIS WHO DEVELOP SBP (The Research of Medical Science Review, 2025)
OBJECTIVES: This study aimed to evaluate the effectiveness of non-selective beta blockers (NSBBs) in cirrhotic patients diagnosed with spontaneous bacterial peritonitis (SBP), focusing on in-hospital mortality, recurrence of SBP, and associated complications. METHODOLOGY: A retrospective observational cohort study was conducted at Combined Military Hospital (CMH), Sialkot. Medical records of 236 adult patients with confirmed liver cirrhosis and SBP were reviewed. Patients were divided into two groups: Group A (n = 112) received NSBBs at the time of SBP diagnosis, while Group B (n = 124) did not. Demographics, liver function tests, ascitic fluid analysis, and clinical outcomes were recorded. Statistical analysis was performed using SPSS version 25, with multivariate logistic regression adjusting for MELD score, age, and comorbidities. RESULTS: The mean age was 54.3 ± 11.2 years, and 62% of patients were male. Group A showed significantly lower in-hospital mortality (13.4% vs. 25.0%, p = 0.024), reduced incidence of hepatorenal syndrome (15.2% vs. 29.0%, p = 0.012), and lower recurrence of SBP within 6 months (10.7% vs. 23.4%, p = 0.008). No significant differences were found in hospital stay duration or hepatic encephalopathy. Multivariate analysis confirmed NSBB use was independently associated with better outcomes. CONCLUSION: NSBB use in cirrhotic patients with SBP was linked to improved clinical outcomes, including reduced mortality and SBP recurrence. These findings support a protective role for NSBBs in this setting, though prospective studies are warranted.